2023
DOI: 10.21512/commit.v17i2.8446
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Usefulness, Satisfaction, and Personalization on Subscription Video on Demand Continuance Intentions

Natasya Elora Carissa,
Muhammad Erlangga,
Cindy Sonesha Evik
et al.

Abstract: The rapid development of Subscription Video on Demand (SVoD) services in Indonesia makes it promising. The change in consumers’ behavior from watching movies through television channels and cinemas to online streaming has encouraged industry players to look for innovation. The research aims to analyze factors influencing the intention to continue using SVoD with Netflix as the case study. The research combines two theories, namely Information System Success (ISS) Model and Expectation Confirmation Theory (ECT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
2
3
0
Order By: Relevance
“…The study found that Indonesian Islamic higher education students are generally ready for online learning, have positive attitudes, and have a keen interest in it. These findings are consistent with previous studies that have found that students generally are increasingly comfortable and engaged with online learning (Elfeky and Elbyaly, 2021;Carissa et al, 2023;Ayyoub et al, 2023). The study also found that technological devices and internet connectivity are pivotal in students' readiness for online learning.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The study found that Indonesian Islamic higher education students are generally ready for online learning, have positive attitudes, and have a keen interest in it. These findings are consistent with previous studies that have found that students generally are increasingly comfortable and engaged with online learning (Elfeky and Elbyaly, 2021;Carissa et al, 2023;Ayyoub et al, 2023). The study also found that technological devices and internet connectivity are pivotal in students' readiness for online learning.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the study found that students value the technological advancements, affordability, and intellectually challenging nature of online learning (Sukendro et al, 2020). This is consistent with previous research showing that students are attracted to continuance intention to use online knowledge for its innovative features, costeffectiveness, and ability to provide a stimulating learning environment (Carissa et al, 2023;Legramante et al, 2023;Du et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations